(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The tremendous breakthroughs in technology are revolutionizing traditional teaching approaches and ushering in a new era of education. The current investigation was done to check the attitude of students towards ICT with respect to their gender, socio-economic status (SES) and academic performance. Attitude towards ICT has been taken as dependent variable while Gender “(Male & Female)”, SES “(High & Low)” and Academic Performance “(High & Low)” have taken as independent variables. In the current investigation “Descriptive survey method” was employed. “Multi-stage random sampling technique” was used to choose the sample of 800 sr. sec. school students studying in XI and XII standard in various schools of North West B-II schools of Delhi were taken. Attitude towards ICT Scale Developed by the Investigator herself. “Socio–Economic Status Scale (SESS) (Kalia & Sahu, 2012)” was applied to gather the data. In order to calculate the academic performance scores, the researcher had to rely on the school’s examination record for the students’ prior test scores, specifically their 10th grade results. Three Way ANOVA using a 2×2×2 factorial design was used to examine the collected data. Result of the study revealed that the interaction effect of gender, socio-economic status (SES) & academic performance on attitude of sr. sec. school students towards ICT was found to be significant. This study would benefit students’ overall development in addition to improving the usage of ICT in the classroom.